Synthesis of 3-Phenyl-4[4-(m-nitrophenyl)-N-2-(2’-arylureido / arylthioureido-4’-N-morpholino-s-triazin)-benzo-[6,7]-coumarins and their Applicatiions - J. P. Raval; K. R. Desai (E-Journal of Chemistry)
Several 3 – phenyl – 4 [4-(m – nitrophenyl) – N – 2 - (2’-arylureido /arylthioureido - 4’- N -morpholino-s-triazin)-benzo-(6,7)-coumarins were prepared using 2-(m–nitrophenyl)-3-hydroxy naphthalene, cyanuric chloride, morpholine and various aryl – ureas / aryl – thioureas derivatives to give desired compound. The structures of the compounds were confirmed by elemental analysis and spectral analysis. The antibacterial activities of these compounds have been screened and were also applied as Flourescent Brighteners on Polyester fabrics.